Hyponatremia due to preserved non-osmotic arginine vasopressin secretion in adipsic diabetes insipidus: a case report with review of literature - Yasufumi Seki; Shun Sugawara; Saya Suzuki; Yulia Minakuchi; Kazuhisa Kusuki; Yuzo Mizuno (Endocrine Journal)
Adipsic diabetes insipidus (ADI) is characterized by central diabetes insipidus and an impaired thirst response to hyperosmolality, leading to hypernatremia. Hyponatremia observed in patients with ADI has been considered a complication of desmopressin therapy. Herein, we present a case of impaired thirst sensation and arginine vasopressin (AVP) secretion without desmopressin therapy, in which hyponatremia developed due to preserved non-osmotic AVP secretion. A 53-year-old woman with hypopituitarism, receiving hydrocortisone and levothyroxine, experienced hyponatremia three times over 5 months without desmopressin treatment. The first hyponatremic episode (120 mEq/L) was complicated by a urinary tract infection with a plasma AVP level of 33.8 pg/mL. Subsequent hyponatremia episodes occurred after administration of antipsychotic (124 mEq/L) and spontaneously (125 mEq/L) with unsuppressed plasma AVP levels (1.3 and 1.8 pg/mL, respectively). Hypertonic saline infusion did not affect AVP or copeptin levels. Regulating water intake using a sliding scale based on body weight prevented the recurrence of hyponatremia without the use of desmopressin. Except during infection, plasma AVP levels (1.3 ± 0.4 pg/mL) were not significantly correlated with serum sodium levels (rs = –0.04, p = 0.85). In conclusion, we present a unique case of impaired thirst sensation and AVP secretion in which hyponatremia developed without desmopressin therapy. Preserved non-osmotic AVP secretion, possibly stimulated by glucocorticoid deficiency, may contribute to the development of hyponatremia in patients with ADI.